Protection of Teachers Right to Fair Hearing, Freedom of Expression and Association for National Cohesion in the Management of Primary Education in Kebbi State, Nigeria - Manga, Sani Dantani (NIU Journal of Social Sciences; Vol 4 No 4 (2018): KIU Journal of Social Sciences, Vol. 4 No. 4, December 2018, 2019)
This paper investigated the extent to which teachers right to fair hearing, freedom of expression and association are protected as a strategy for ensuring national cohesion in the management of Primary Education in Kebbi state. The study was a descriptive survey in which 50 primary schools drawn from urban and rural areas in five education zones in Kebbi State were deliberately sampled. The views of 250 teachers and 150 school managers were sampled through stratified and simple random sampling techniques. A self-designed and validated instrument with a reliability index of 0.88 on a four point Likert scale was used. Mean computation and Rank order were used to analyze data to answer research questions using mean of 2.5 and above as the cut-off mean for acceptance and below it for rejection while z-test statistics was used to test the hypotheses at 0.05 level of significance. It was found that to a large extent, teacher’s right to fair hearing, freedom of expression and association were protected in the management of Primary Education in Kebbi State. It was therefore recommended that the protection of teachers’ right should continue to be upheld in order to ensure national cohesion, not only in Kebbi State but in Nigeria as a whole. Keywords: Protection, Teachers Right, Fair hearing, Freedom of expression, Association, National Cohesion, Management.